Patient characteristics, comorbidities, and medication use for children with ADHD with and without a co-occurring reading disorder: A retrospective cohort study - Classi Peter M; Le Trong K; Ward Sarah; Johnston Joseph (BMC, 2011)
Abstract Background Children and adolescents with attention-deficit/hyperactivity disorder (ADHD) often have a co-occurring reading disorder (RD). The purpose of this research was to assess differences between children with ADHD without RD (ADHD-only) and those with ADHD and co-occurring RD (ADHD+RD). Methods Using data from the U.S. Thomson Reuter Marketscan® Databases for the years 2005 through 2007, this analysis compared the medical records--including patient demographics, comorbidities, and medication use--of children (age < 18) with ADHD-only to those with ADHD+RD. Results Patients with ADHD+RD were significantly younger, more likely to have received a procedure code associated with formal psychological or non-psychological testing, and more likely to have been diagnosed with comorbid bipolar disorder, conduct disorder, or depression. They were no more likely to have received an antidepressant, anti-manic (bipolar), or antipsychotic, and were significantly less likely to have received a prescription for a stimulant medication. Conclusions Relying on a claims database, there appear to be differences in the patient characteristics, comorbidities, and medication use when comparing children with ADHD-only to those with ADHD+RD.